The shepherd's view : modern photographs from an ancient landscape - Rebanks, James (Flatiron Books, 2016)
"From The New York Times bestselling author of The Shepherd's Life, a breathtaking book of photography and wisdom that chronicles an ancient way of living that deeply resonates in our modern world. With over eighty full color photographs The English Lake District comes into full focus: the sheep competitions of the spring, the sweeping pastures of the summer, beloved sheep dogs in the fall and the harsh snows of winter. A celebration of a way of life still very much alive, The Shepherd's View is a poetic, and artistic achievement from one of England's most celebrated new voices,"--Amazon.com.